2023
DOI: 10.1371/journal.pone.0282318
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome among health care workers during the COVID-19 pandemic. A cross sectional study in Monastir, Tunisia

Abstract: Background Burnout syndrome may affect the safety of frontline healthcare care workers (HCW) and patients. We aimed to measure the prevalence of burnout among HCW in care facilities in Tunisia during the Covid-19 pandemic and to identify its associated factors. Methods We conducted a cross-sectional study among HCW practicing during the covid-19 pandemic in health care facilities in the governorate of Monastir. Data collection was carried out using an anonymous self-administered questionnaire composed by thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A total of 89.14% of the participants in our study reported experiencing burnout, 31.46% of whom had moderate to high burnout. Previous studies have shown that the incidence of burnout among HCWs was up to 84.44% [ 55 ] and that the incidence of moderate to high burnout was 50.13% [ 56 ]. Burnout during the full relaxation of COVID-19 restrictions was much more prevalent but less severe among HCWs than before their relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 89.14% of the participants in our study reported experiencing burnout, 31.46% of whom had moderate to high burnout. Previous studies have shown that the incidence of burnout among HCWs was up to 84.44% [ 55 ] and that the incidence of moderate to high burnout was 50.13% [ 56 ]. Burnout during the full relaxation of COVID-19 restrictions was much more prevalent but less severe among HCWs than before their relaxation.…”
Section: Discussionmentioning
confidence: 99%